COMPUTER MODELING AND NUMERICAL EXPERIMENT TO STUDY THE INFLUENCE OF COMPOSITION STRUCTURES SPILLWAY FRONT OF A DAM ON THE VALUE OF THE SPECIFIC EXPENSES - Z. A. Kurbanova (Вестник Дагестанского государственного технического университета: Технические науки)
Because of absence in normative documents of techniques and recommendations for definition of specific economic expenses of overflow dams, taking into account all accompanying constructions of a flutbett, in design practice the simplified and approximate method of alternative design is used. As a result of researches graphic dependences of cost on specific economic expenses of low pressure overflow dams on not rocky basis at various structure of constructions are received.